2016
DOI: 10.1002/aur.1663
|View full text |Cite
|
Sign up to set email alerts
|

Children with autism spectrum disorder have reduced otoacoustic emissions at the 1 kHz mid‐frequency region

Abstract: Autism spectrum disorder (ASD) is a behaviorally diagnosed disorder of early onset characterized by impairment in social communication and restricted and repetitive behaviors. Some of the earliest signs of ASD involve auditory processing, and a recent study found that hearing thresholds in children with ASD in the mid-range frequencies were significantly related to receptive and expressive language measures. In addition, otoacoustic emissions have been used to detect reduced cochlear function in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Even when audiological data are collected, unique features associated with ASD can make the data difficult to interpret. Specifically, studies suggest that both behavioral and physiological clinical tests may have different results for children with ASD compared to children that are neurotypical (Bennetto, Keith, Allen, & Luebke, 2017;Kwon, Kim, Choe, Ko, & Park, 2007;Roth, Muchnik, Shabtai, Hildesheimer, & Henkin, 2012;Tharpe et al, 2006). It appears that these differences are not a result of peripheral hearing loss but rather are due to potential underlying differences in auditory functioning and/or structural differences in the brain (e.g., Hyde, Samson, Evans, & Mottron, 2010;Kulesza, Lukose, & Stevens, 2011;Kulesza & Mangunay, 2008;Kwon et al, 2007;Roth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when audiological data are collected, unique features associated with ASD can make the data difficult to interpret. Specifically, studies suggest that both behavioral and physiological clinical tests may have different results for children with ASD compared to children that are neurotypical (Bennetto, Keith, Allen, & Luebke, 2017;Kwon, Kim, Choe, Ko, & Park, 2007;Roth, Muchnik, Shabtai, Hildesheimer, & Henkin, 2012;Tharpe et al, 2006). It appears that these differences are not a result of peripheral hearing loss but rather are due to potential underlying differences in auditory functioning and/or structural differences in the brain (e.g., Hyde, Samson, Evans, & Mottron, 2010;Kulesza, Lukose, & Stevens, 2011;Kulesza & Mangunay, 2008;Kwon et al, 2007;Roth et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a growing debate in the literature about whether physiological data are clinically different for children with ASD. Compared to children who are neurotypical, children with ASD may have longer ABR latencies (Kwon et al, 2007;Roth et al, 2012; for contradictory findings, see Courchesne, Courchesne, Courchesne, & Lincoln, 1985;Dunn, Gomes, & Gravel, 2008;Tharpe et al, 2006) and reduced responses for OAEs (Bennetto et al, 2017;Danesh & Kaf, 2012; for contradictory findings, see Gravel, Dunn, Lee, & Ellis, 2006;Tharpe et al, 2006). Although the underlying mechanisms for abnormal findings are not clear, it has been suggested that differences may be attributed to overall structural brain differences (Hyde et al, 2010;Kulesza & Mangunay, 2008;Kulesza et al, 2011;Kwon et al, 2007;Roth et al, 2012).…”
Section: Challenges Associated With Testing and Interpreting Audiologmentioning
confidence: 99%
“…They may also confirm a persisting cochlear hearing loss because of outer hair cell dysfunction in babies (Janssen, 2013). Reduced DPOAE responses have been observed in clinical groups of children with severe communication disorders, such as autism (Bennetto et al, 2017) and Williams syndrome (Silva et al, 2018). However, few studies have incorporated DPOAEs in their hearing evaluation of children with SSD.…”
Section: Middle Ear Sound Energy Transmittance -Developmental Aspectsmentioning
confidence: 91%
“…However, two recent studies on clinical populations of children with autism, have found dips within the key frequencies of speech. For example, Demopoulos and Lewine (2016) found reduced hearing thresholds at 2 kHz in children 5-18 years with autism, and Bennetto et al (2017) found reduced otoacoustic emissions at 1 kHz in 6-17-year-old boys with autism. Demopoulos and Lewine (2016) also demonstrated a relationship between pure-tone auditory thresholds within the key-frequencies for speech, and expressive and receptive language measures.…”
Section: Key-frequencies For Speechmentioning
confidence: 99%
See 1 more Smart Citation